Market Power and Export Taxes - Jean-Marc Solleder (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper explores the extent to which market power considerations explain levels of export taxes. Market power is proxied by the inverse import demand elasticities faced by exporters. The paper first provides estimates of market power for exporting countries and products at the 6-digit level of the Harmonized System. It then finds a positive correlation between market power and export taxes. This result supports the theory that, when unconstrained in their trade policy choices, countries take their market power into account when setting their export taxes.
Keywords: 330; Market power; export taxes; export policy; import demand elasticities